Pengaruh Gaya Kepemimpinan Dan Komunikasi Terhadap Semangat Kerja Pegawai Pada Badan Perencanaan Pembangunan Daerah (Bappeda) Kota Bima - Marsina Marsina; Mukhlis Mukhlis (Sekolah Tinggi Ilmu Ekonomi Surakarta, 2022)
This research is motivated by the spirit of the employees not being fully optimal, which can be seen from the work that cannot be completed in accordance with the time determined by the agency, besides that there is still a lack of acceleration of task completion and the ability to develop an activity agenda that prioritizes work support needs for equipment. area. This is caused by the lack of optimal leadership and communication styles. This type of research is associative research. The total population in this study were all civil servants at the Regional Development Planning Agency of Bima City, which amounted to 38 employees. In this study, data collection was carried out through several techniques, namely library research, field studies and distributing questionnaires. From the results of the study, a conclusion can be drawn as follows: There is an influence of leadership style on work spirit at the Regional Development Planning Agency of Bima City. This means that if the leadership style is good, employee morale will increase. There is an influence of employee communication on work spirit at the Regional Development Planning Agency of Bima City. This means that if the employee's competence is high, the employee's morale will increase; there is no simultaneous influence of leadership style and employee communication on work spirit at the Regional Development Planning Agency of Bima City